Music as an ergogenic aid in team sports: a systematic review - Bezuglov, Eduard; Vakhidov, Timur; Kapralova, Elizaveta; Malyakin, Georgiy; Vinogradov, Mikhail; Chyogin, Sergey; Butovskiy, Mikhail (Frontiers in Sports and Active Living, 2025)
ObjectivesEnhancing physical performance and improving load tolerance through safe methods is a priority for most athletes. One potentially beneficial approach is listening to music, which exerts positive effects through various mechanisms. This study aims to investigate the influence of music on athletic performance and endurance, focusing specifically on its potential as an ergogenic aid in team sports—an area that has received less attention compared to individual sports.MethodsTo examine the effects of music on physical performance and load tolerance in team sports athletes, we conducted a systematic search for original English-language articles in PubMed, Mendeley, and the Cochrane Library from inception to June 2024, following PRISMA guidelines.ResultsThe search identified eight studies that met the inclusion criteria, involving 140 participants from football, volleyball, and basketball. All studies demonstrated a low risk of bias. None of the studies included elite adult international-level athletes. The analysed parameters included peak power, sprint and jump performance, maximal oxygen consumption, repeated sprint ability, change of direction, and load tolerance indicators such as heart rate, rating of perceived exertion (RPE), and fatigue index. Most studies demonstrated a significant positive effect of music on these parameters; however, the protocols for music accompaniment were not standardised.ConclusionThe findings suggest that music can positively impact both physiological and psychological factors, though its application in team settings requires further investigation. Given its safety and accessibility, music may serve as a valuable tool for enhancing performance in various sporting contexts. Future studies should include more detailed information on music usage protocols and involve larger sample sizes, particularly including adult elite athletes.